Ethical and legal dimensions of informed consent in aesthetic conservative dentistry: a review under Indonesia’s health law - Fauziah, Yessy Andriani; Darmadi, Eveline Yulia; Yemy Ameliana; Wahjuningrum, Dian Agustin; Susanto, Dany Agus (Conservative Dentistry Journal, 2025)
Background: Aesthetic treatments in conservative dentistry, such as tooth whitening, veneers, and composite restorations, have become increasingly popular as more patients seek to enhance their appearance. Unlike therapeutic procedures, these treatments are often elective and based on personal preferences, which brings forward important ethical and legal questions. One of the key aspects is how dentists ensure that patients truly understand the benefits, risks, and alternatives before making a decision. Purpose: This review aims to examine the ethical and legal dimensions of informed consent in aesthetic conservative dentistry, with particular reference to Indonesia's Law No. 17/2023 concerning Health. It explores how dental professionals are expected to balance patients' aesthetic desires with ethical responsibilities and legal duties. Reviews: The discussion covers core ethical principles, including autonomy, beneficence, nonmaleficence, and justice as the foundation of a meaningful consent process. It also examines the latest national regulation, which outlines patient rights and dentist responsibilities, particularly Law No. 17/2023 concerning Health. Since aesthetic procedures are not always medically necessary, they require extra care in communication and documentation to ensure proper patient care and treatment. Conclusion: Informed consent in aesthetic dental care should not be treated as a formality. It is a vital ethical practice that ensures patients feel respected and well-informed. For dentists, especially those involved in aesthetic procedures, it is important to apply both ethical reflection and legal awareness in every step of patient care. Following Law No. 17/2023 concerning Health, maintaining open and honest communication fosters trust and supports safe, responsible treatment.